Penerapan sistem informasi akuntansi dalam mendukung pengendalian internal pemberian kredit pada Bank Perkreditan Rakyat Millenia Bank Kota Manado - Ginting, Amparwati; Alexander , Stanly W.; Kapojos , Peter M. (Riset Akuntansi dan Portofolio Investasi, 2024)
Millennia People's Credit Bank is facing problems that have a significant impact on the health of the bank, namely issues such as substandard credit, which often occur. This risk could cause Millenia Rural Bank to experience losses. To mitigate this risk, the bank must conduct a thorough credit analysis to support internal controls in making decisions to accept or reject prospective customers' credit applications. The type of research used in this study is descriptive qualitative. In the accounting information system, procedures for granting BPR Millenia credit, from submitting a credit application to disbursing credit funds, have been carried out properly and in accordance with applicable procedures. The accounting information system at PT. Millenia Rural Bank plays a very important role in carrying out credit providing activities. With an accurate accounting information system, employees at PT. Millennia People's Credit Bank can easily obtain the data and documents needed before the credit granting process.